Application of Moving Class Learning Models and Teacher Pedagogical Competence on Learning Motivation and Student Learning Discipline - Marina Marina; Henny Indrawati; Suarman Suarman (Universitas Riau, 2019)
This study aims to analyze the effect of the application of moving class learning models and pedagogical competencies of teachers on learning motivation and its impact on student learning discipline in SMP Negeri 2 Bandar Seikijang. The population of this research were 151 students of class VIII and IX. Sampling method used proportional random sampling using the Slovin formula, so as to obtain 110 students. Data collection used a questionnaire with a Likert scale. The data analysis technique used a path analysis. The results of the analysis show that the application of the moving class learning model and the pedagogical competition of the teacher have a positive and direct and indirect effect on student learning discipline through intervening variables (learning motivation). In accordance with the results of the observation, the dominant contribution to the increase in motivation and discipline of students to learn is the presence of pedagogical competence of the teacher while the application of the moving class learning model only makes a smaller contribution. This shows that the good or bad quality of the teacher's pedagogical competencies and the moving class learning model will also reduce or increase student learning motivation which has an impact on student learning discipline.